The implementation of project management processes and its relationship with project success in the Malaysian interior design sector / Kashini Mahenthiran - Kashini, Mahenthiran (2022)
The work of an interior designer revolves around the design, construction and management of the project. Therefore, the knowledge and understanding with regards to project management, technicality and system of work is required in order to deliver projects successfully. However, existing literature shows insufficient documented knowledge and information with relation to the implementation of project management processes in interior design projects. The basic attention of available literature on this topic is mostly directed towards specific issues faced in the lifetime of interior design projects with studies on its possible solutions, but very little information has been found on the overall management of these projects to curb those issues. The review of literature also exposed a lack of information and research with relation to project management in the interior design sector and its relationship with project success. Thus, the aim of this research is to study the implementation of project management processes in interior design projects and its relationship to project success. The research approach adopted in this study is the deductive approach whereby the theory is established first through an extensive literature review before empirical research and analysis is based on quantitative data collected from 86 interior design professionals using an online questionnaire survey. It is anticipated that this study will establish the implementation of project management processes in interior design projects in Malaysia as well as assist in proving the importance and contribution of project management in influencing interior design project success, and later, identifying potential opportunities of interior design management.